The Digital Mediation of Teacher’s Feedback: Investigating the Efficacy of Screen-Cast Video Feedback on EFL Learners’ Writing Revision and Self-Efficacy - Mohamed Elsayed Abdou Seddik (Journal of English Language and Education, 2026)
The provision of effective written corrective feedback (WCF) remains a persistent pedagogical challenge in EFL contexts, often constrained by time, clarity, and learner engagement. While digital tools offer new avenues, their localized efficacy in resource-aware settings like Egyptian public schools is underexplored. This quasi-experimental study investigated the impact of screen-cast video feedback (SVF)—a blend of audiovisual and screen casting commentary—compared to traditional written feedback (TWF) on the writing revision quality and writing self-efficacy of Egyptian secondary school students. Conducted over three weeks in a public school in Mansoura, Egypt, the study involved 60 participants divided into control (TWF) and experimental (SVF) groups. Data sources included pre-/post-test writing samples scored with a rubric, a writing self-efficacy scale, and semi-structured interviews. Quantitative analysis (MANCOVA) revealed that the SVF group produced statistically significant improvements in revision accuracy, particularly in addressing global issues (e.g., organization, thesis clarity) and complex grammatical errors. Furthermore, the SVF group demonstrated a significant increase in writing self-efficacy. Qualitative analysis highlighted that SVF was perceived as more personalized, comprehensible, and engaging, fostering a stronger teacher-student connection. The study argues that SVF, as a multimodal feedback form, aligns with principles of cognitive load theory and sociocultural approaches by making feedback more accessible and dialogic. It concludes that SVF is a pedagogically viable and effective alternative for EFL writing instruction in contexts similar to Egypt, advocating for its integration despite infrastructural constraints.